An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Codigestion of food waste and real traditional Chinese medicine wastewater in anaerobic membrane bioreactor: Stability mechanism and microbial community dynamics - Yong-Xin Cui; Bao-Shan Xing; Su Li; Zi-Yi Wang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Artemselenolides I–N, sesquiterpenoid trimers from Artemisia selengensis with antihepatoma activity – structural elucidation, molecular docking and dynamics studies - Rong-Kai Chen; Tian-Ze Li; Yong-Cui Wang; Yun-Bao Ma; Ji-Jun Chen (Phytochemistry, 2026)

Extractant-immobilized dendritic fibrous nanosilica for rapid and selective rare-earth separation from complex aqueous matrices - Fang Zhang; Yuxin Zong; Hongwei Rong; Baihui Cui; Luchun Duan; Pamphile Ndagijimana; Akash Kumar; Jean Claude Hakizimana; Fidele Dusangumukiza; Dabin Guo; Ravi Naidu; François Nkinahamira (Desalination, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Low-velocity mudstone identification using well logs and prestack seismic data based on principal component analysis and multilayer perceptron - Mengyu Ren; Xuri Huang; Xiaoqing Cui; Ran Yang; Rong Zhang; Jingshi Liu; Chaoyi Niu (Journal of Applied Geophysics, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Iodine vapor adsorption induced liquid conductive metal-organic frameworks for self-powered humidity sensing - Weifang Zhang; Yuan Cheng; Lingling Zhuang; Ruijin Jiang; Cui-Cui Ji; Rong-Rong Xie; Yupeng Chen (Chemical Engineering Journal, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Dysregulation of xenobiotic metabolism and mitochondrial dysfunction exacerbate acetaminophen-induced hepatotoxicity in human antigen R-deficient male mice - Natalie Eppler; Elizabeth Jones; Forkan Ahamed; Naren Raja; Jephte Y. Akakpo; Margitta Lebofsky; Lily He; Ira Vats; Priyanka Ghosh; Yifan Yu; Kaitlyn Thomas; Colin McCoin; et al. (Toxicology, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

A 3D sp2-carbon-conjugated hydrogen-bonded COF platform for reductive gold capture and photocatalytic detoxification of a chemical warfare simulant - Xiao-Yi Fan; Xiu Wang; Yong Zhang; Wei-Bin Qiu; Wei-Rong Cui (Chemical Engineering Journal, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Manure compost and gypsum amendments revitalize soil quality via aggregation and pore structure in the Yellow River Delta - Xiaoyang Duan; Xiaoying Jin; Qi Miao; Zhanlonggang Yu; Hui Rong; Xiao Wang; Zhenling Cui; Hu Zhou; Zhangliu Du (Journal of Soils and Sediments, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Effects of coupled environmental factors on rubber properties in polar region - Jiaojiao Cui; Rong Huang; Shihong Hu; Meng Cui; Wei Sun (Ocean Engineering, 2026)

Ultrafast and selective recovery of rare earths from aqueous streams using a P507-scaffolded dendritic nanosilica - Fang Zhang; Yuxin Zong; Hongwei Rong; Baihui Cui; Luchun Duan; Pamphile Ndagijimana; Moses Akintayo Aborisade; Ghazanfar Mehboob; Dabin Guo; Ravi Naidu; François Nkinahamira (Journal of Cleaner Production, 2026)

Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Uneven geographies, contested practices: The politics of knowledge production in Chinese urban studies - Rong Yang; Chen Cui; Zhenjie Yuan; Hong Zhu (Applied Geography, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Multi-physical field coupling cavitation state research and evolution prediction - Xiaoyu Wang; Rong Cui; Tian Wang; Haobin Hu; Shenghao Zhou; Guiming Ye (Ocean Engineering, 2026)

Foliar silicon application enhances rare earth element accumulation in the hyperaccumulator Phytolacca americana - Rui-Qi Zhang; Cui-Ling Huang; Ling-Xiu Zhou; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Environmental Sciences, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

Gelation behavior of egg white protein modulated by polysaccharide charge characteristics: Molecular mechanisms from hydration perspective - Can Wu; Rong He; Xinyu Liu; Qiuyue Hou; Bing Cui; Bin Zhou (Food Chemistry, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Settling and dewatering characteristics of super absorbent polymer treated fine-grained dredged sediment waste - Yupeng Cao; Jie Yin; Xinzhuang Cui; Zhehao Qiu; Shuai Zhang; Rong Wang (Journal of Soils and Sediments, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Novel metabolic pathway of skatole degradation by Enterococcus hirae IDO5 and its application in swine manure wastewater treatment - Yanzhi Lin; Yanchen Liu; Xianyong Ma; Miao Yu; Yiyan Cui; Guangying Weng; Jing Yu; Ting Rong; Zhichang Liu; Dun Deng; Min Song (Journal of Hazardous Materials, 2026)

Highly efficient removal and detoxification of ochratoxin a in wine via adsorption-photocatalytic synergy of polymerized dopamine-wrapped magnetic titanium dioxide - Saiqun Wang; Keying Chu; Rong Guo; Yue Liu; Lu Cui; Zhouli Wang; Xubo Zhao (Food Chemistry, 2026)

Mediating role of metabolic dysfunction-associated fatty liver disease in the association between individual-level noise exposure and liver enzymes in Chinese automotive manufacturing workers - Sijia Ou; Jiaheng Yu; Zhaoqian Chen; Yanmei Ruan; Xing Rong; Zejin Ou; Yuxia Zhang; Haijuan Huang; Jiaxin Cui; Zhi Wang (International Archives of Occupational and Environmental Health, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Dissolution-reprecipitation mechanism of clay-type lithium ore in low temperature two-stage mixed acid leaching - Rong Huang; Jian Liu; Jiamei Hao; Hulin Gao; Bao Cui (Journal of Environmental Chemical Engineering, 2026)

Directional selection mechanism of single atom catalyst Co-S-C/CB regulating peroxymonosulfate radical pathway - Bin Ou; Hongwei Rong; Baihui Cui; Jie Zhang; Fang Zhang; Dabin Guo (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Effect of freeze–thaw treatment on physicochemical and antioxidant properties of Chinese hawthorn fruit and its juice - Rong Li; Chang Ma; Falong Du; Jiawei Cui; Yunfeng Hu; Junran Chen (Food Chemistry, 2026)

Rapid quantitative real-time analysis and visual detection of Escherichia coli in meat by direct PMAxx-VPCR - Jiaqi Cui; Tingting Zhao; Wenjun Song; Huilin Li; Yan Chen; Rong Chen (Food Control, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

5-Methoxyflavone inhibits the proliferation of lung adenocarcinoma cells through PI3K/AKT/GSK3β/β-catenin/Cyclin D1 signaling and attenuates chemoresistance and PD-L1 expression - Yan Zhao; Yiwen Cui; Rong Li; Mingyong Li; Zhiwei He; Yingying Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Spatiotemporal evolution and resilience optimization of urban ecological networks: A case study of the Xiong'an New Area - Lixiang Wen; Junhong Bai; Yuejing Rong; Langying Long; Changhong Xiao; Yanan Guan; Baoshan Cui (Journal of Cleaner Production, 2026)

Molecular weight-engineered polyelectrolyte boosts charge carrier mobility for enhanced photocatalytic antibiotic removal - Qingyang Xu; Rong Wang; Derui Liang; Yi Wang; Ke Cui; Xue Yang; Jingyi Chen; Huaizhi Shao; Qian Zhang; Hailin Cong (Journal of Environmental Management, 2026)

The role of farm size in public goods provision: An agent-based model of habitat conservation in agricultural landscapes - Rong-Gang Cong; Jia-Rui Cui (Journal of Environmental Management, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Cover cropping shifts microbial life-history strategies to promote necromass carbon accumulation through soil metabolite mediation in orchard systems - Yutao Zhang; Jia Liu; Kailou Liu; Daming Li; Rong Cui; Yaxin Liu; Xingjia Xiang; Ming Liu (Soil and Tillage Research, 2025)

Discriminating the impact of soil moisture and vapor pressure deficit on vegetation greening over multiple time scales - Zijun Wang; Rong Wu; Jiazheng Li; Yangyang Liu; Chenfeng Cui; Junrong Liu (Global and Planetary Change, 2025)

Food defect detection technologies based on deep learning and prospects in detection of unsound wheat kernels - Rong Wang; Zhiyao Zhao; Ying Sun; Yongbiao Ni; Jin Ye; Min Zhang; Liwen Cui (Food Chemistry, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

LRRC8A/PKC/FLNA pathway activation is detrimental to colon cancer patients - Rong Liu; Lijuan Zhao; Shiyu Cui; Masoud Pouranfard; Zhenghui Jing; Yuhua Ren; Wenbao Zhao; Dangxia Zhou; Haifeng Zhang (Functional & Integrative Genomics, 2025)

Carbon-ferric based coagulants for enhanced removal of turbidity, bisphenol A, and tetracycline from synthetic wastewater - Jean Claude Hakizimana; Yongkang Ye; Fang Zhang; Pamphile Ndagijimana; François Nkinahamira; Fidele Dusangumukiza; Hongwei Rong; Jingying Wang; Baihui Cui; Dabin Guo (Journal of Water Process Engineering, 2025)

Compartment engineering in yeast: a path to increased biochemical production - Yuyang Wang; Liyan Cao; Lanxin Rong; Chen Ding; Chang Liu; Qingqing Ye; Qingeng Huang; Cui-ying Zhang; Ning Xu; Jiwei Mao; Jee Loon Foo; Aiqun Yu (Chemical Engineering Journal, 2025)

Fluoride Induces Spermatogonial Apoptosis via IP3R-MCU-Mediated Mitochondrial Calcium Overload - Rong Wang; Han Wang; Wenjing Gong; Xiaoqian Chen; Mengli Zheng; Ya Cui; Chunmei Liang; Jiayue Hu; Yuanhua Chen; Yanli Ji (Biological Trace Element Research, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

A hydraulic conductivity model for unsaturated bentonite-based materials incorporating surface enhanced vapour diffusion - Zhang Rong LIU; Yu Jun CUI; Wei Min YE; Yong Gui CHEN; Qiong WANG (Computers and Geotechnics, 2025)

Analysis of starch structure, functional properties, and the underlying molecular mechanism in SeaRice86 (SR86) - Yongxiang Huang; Xiao Yang; Yilan Cui; Mangu Hu; Yunliang Rong; Yu Ling; Rongchao Yang; Yueqin Zhang (Carbohydrate Polymers, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Metatranscriptomic insights into nitrogen loss mediated by multi-kingdom microbial interactions in periphytic biofilms under imidacloprid exposure - Zuqiang Cao; Juan Chen; Chao Wang; Peifang Wang; Han Gao; Bingbing Feng; Bo Zhang; Rong Wang; Ge Cui (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Mechanisms of naphthalene biodegradation in microalgal-bacterial co-culture systems: role of photosynthesis, antioxidant and extracellular polymeric substances - Mengying Wang; Han Wang; Xuetao Liang; Lingyun Rong; Longyan Cui; Chen Wang; Sixu Wang; Qi Yang; Zhilin Yang (Journal of Cleaner Production, 2025)

Synergistic electrostatic, coordination, and redox mechanisms in cationic covalent organic frameworks for ultrafast and selective gold recovery - Meng-Yao Zhou; Xiu Wang; Shun-Hao Zeng; Qian-Qian Zhao; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Bridging the knowledge gap: From poly(butylene adipate-co-terephthalatebutylene) degradation to CO2-generating mineralization under the synergistic effect of bacteria and fungi - Yue Wang; Qi Liu; Chang-Hong Xie; Ruo-Tong Zhao; Qiu-Xiang Tang; Dong-Fei Han; Yi-Ning Xia; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Degradation of biodegradable plastic films in soil: microplastics formation and soil microbial community dynamics - Yue Wang; Run-Hao Bai; Qi Liu; Qiu-Xiang Tang; Chang-Hong Xie; Aurore Richel; Christophe Len; Ji-Xiao Cui; Chang-Rong Yan; Wen-Qing He (Journal of Hazardous Materials, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Integration of comparative cytology, ionome, transcriptome and metabolome provide a basic framework for the response of foxtail millet to Cd stress - Jie Zheng; Xinyue Wang; Rong Huang; Peiyu Xian; Jian Cui; Aduragbemi Amo; Liang Chen; Yuanhuai Han; Siyu Hou; Yang Yang (Journal of Hazardous Materials, 2025)

Modulation of surface properties and emulsifying properties of gliadin particles by alkyl gallates: Effects of pH and alkyl chain length - Can Wu; Ziqing Zhao; Rong He; Xinyu Liu; Bing Cui; Yuying Hu; Bin Zhou (Food Research International, 2025)

Effect of culturing factors on the production of biomass and secondary metabolites in ginseng adventitious root cultures for new resource food - Hang-Lin Song; Zheng-Hai Cheng; Rong-De Jin; Chun-Guang Liu; Xiang-Hong Ma; Jun-Nan Wu; Xi-Hua Cui (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Upregulation of WDR4 mediated by RBFOX2 promotes laryngeal cancer progression through the WDR4/m7G/lncRNA ZFAS1/RBFOX2 axis - Baocai Lu; Xiao Li; Wenjie Miao; Qi Liu; Ruixue Li; Can Cui; Qingzu Gao; Rong Lian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A sudden drop in temperature causes an imbalance in skin mucus barrier homeostasis in grass carp (Ctenopharyngodon idella) - Yali Wang; Xiaoning Gao; Zihao Cheng; Rong Chen; Yangyang Zhang; Subin Cui; Siyu Zhang; Kun Hu; Congdi Wu (Aquaculture, 2025)

Variation in climate and hydrological conditions in Southwest China during the mid-to-late Holocene, inferred from stalagmite multiple proxies - Hua-Yan Li; Yao Wu; Ting-Yong Li; Rong Duan; Hai-Bo Wang; Jia-Hui Cui; Chao-Jun Chen; Yue Jin; Yue-Hua Xiang; Zi-Qi Liu; Jun-Yun Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Recruitment of copiotrophic and autotrophic bacteria by hyperaccumulators enhances nutrient cycling to reclaim degraded soils at abandoned rare earth elements mining sites - Yong-He Han; Xi-Wen Cui; Hai-Yan Wang; Xiao-Bin Lai; Ying Zhu; Jia-Bing Li; Rong-Rong Xie; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Hazardous Materials, 2025)

Ultrafast self-gelling, superabsorbent, and adhesive chitosan-based hemostatic powders for rapid hemostasis and wound healing - Ashuang Liu; Shengyong Cui; Lei Song; Xiangshu Guo; Zhimao Huang; Shancan Wang; Kai Cheng; Ying Xiao; Youfen Fan; Rong Wang (Carbohydrate Polymers, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Food-driven transformation of nitrogen fluxes with urbanization in China - Ouping Deng; Jiale Wei; Jinglan Cui; Shuai Huang; Luxi Cheng; Rong Huang; Baojing Gu (Resources, Conservation and Recycling, 2025)

Extraction of short-chain fatty acid ethyl Ester in Baijiu using covalent organic framework–based magnetic nanoparticles: Theoretical screening and experimental validation - Xiaolong Shang; Ying Han; Xudong Lian; Siting Ye; Ling Ao; Baoguo Sun; Rong Liu; Pan Zhen; Yongqing Zhang; Yintao Jia; Wei Dong; Xiaotao Sun; et al. (Food Chemistry, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

3D reconstruction of a million atoms by multiple-section local-orbital tomography - Liangze Mao; Jizhe Cui; Rong Yu (Science Bulletin, 2025)

Advances in carbon-based materials for solar-driven steam generation, desalination and water treatment - Pamphile Ndagijimana; Baihui Cui; Xuehua Zhang; François Nkinahamira; Hongwei Rong; Dabin Guo; Benoit Rugabirwa; Jean Claude Hakizimana; Pancras Ndokoye; Jean Claude Nizeyimana (Desalination, 2025)

Physical hydrogel evaporators with uniformly dispersed hydrophobic components for freshwater and electricity cogeneration - Lichao Jiang; Honglang Lu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2025)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

Coupling polyethylene microplastics with other pollutants: Exploring their combined effects on plant health and technologies for mitigating toxicity - Linmei Cui; Rong Liang; Chi Zhang; Ruifang Zhang; Hong Wang; Xin-Xin Wang (Science of The Total Environment, 2024)

Applicability analysis of comprehensive drought index based on GRACE data in ten major river basins in China - Rong Wu; Zijun Wang; Chenfeng Cui; Yongxiang Li; Miao Tang; Jiangdong Chu; Renjie Xv; Chenrui Zhu; Shuo Wang; Yuli Li; Chengyuan Zhang; Zhannan Huang (Journal of Hydrology, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Construction of Bi5O7I/Bi3O4Br heterojunction with abundant oxygen vacancies to enhance photocatalytic performance - Jian Feng; Xia Ran; Li Wang; Bo Xiao; Keqin Zhang; Jinming Zhu; Zuoji Liu; Chaozhong Li; Xinai Cui; Rong Li; Guangwei Feng (Journal of Environmental Chemical Engineering, 2024)

Towards advanced removal of organics in persulfate solution by heterogeneous iron-based catalyst: A review - Baihui Cui; Tingting Tian; Luchun Duan; Hongwei Rong; Zhihua Chen; Shiyi Luo; Dabin Guo; Ravi Naidu (Journal of Environmental Sciences, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Optimizing interactions for efficient hydrogen evolution reaction by incorporating rhenium nanoparticles on defect-rich carbon - Yi-Sha Ba; Wen Lei; Xin Du; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Biodegradable MAM-based amphiphilic block copolymers: Toward efficient and eco-friendly kinetic inhibitors for methane hydrate formation - Li Wan; Xiang-Long Ding; Ai-Xiang Liu; Hao Cui; Jin-Rong Zhong; Yi-Min Dai (Chemical Engineering Journal, 2024)

Exploring the integrated potential of pyrolysis and low-temperature wet torrefaction for typical medical waste valorization: A multifaceted approach leveraging online TG-FTIR-MS, 2D-COS, iso-conversional kinetics, and reaction mechanisms - Akash Kumar; Lata Kumari; Azhar Ali Laghari; Hongwei Rong; Imtiaz Ali Jamro; Shahdev Sajnani; Moses Akintayo Aborisade; Gulzeb Rajput; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Ghazanfar Mehboob; et al. (Chemical Engineering Journal, 2024)

TAF15 inhibits p53 nucleus translocation and promotes HCC cell 5-FU resistance via post-transcriptional regulation of UBE2N - Jiayan Fang; Mengqi Zou; Mei Yang; Yejia Cui; Rong Pu; Yufeng Yang (Journal of Physiology and Biochemistry, 2024)

Effects of microplastics on potato verticillium wilt and microbial community of rhizosphere soil - Naqi Cui; Hongwu Liang; Weisong Zhao; Mingzhu Zhao; Yu Wang; Qinggang Guo; Zihui Rong; Shezeng Li; Ping Ma (Applied Soil Ecology, 2024)

Optimizing shrimp nutrition and health: ginseng saponins as functional additives in low-fishmeal diets on Litopenaeus vannamei - Sihan Lin; Rong Yao; Xin Cui; Yucai Guo; Denghui Hu; Bin Zhou; Zhaobin Zhou; Xuanshu He; Zhihong Liao; Beiping Tan; Jin Niu (Frontiers in Marine Science, 2024)
The research investigated the nutritional physiology effect of ginseng saponins on Litopenaeus vannamei ( L. vannamei ) under low-fishmeal diets. In total, five experimental groups were arranged, with 21% fishmeal (high-fishmeal) serving as the positive control (PC), 11% fishmeal (low-fishmeal) serving as the negative control (NC), and 11% fishmeal serving as the addition in all three other groups. Similarly, ginseng saponins (GSP, purity of 2%) were added in the order of 0.1%, 0.3%, and 0.5% (GSP0.1, GSP0.3, and GSP0.5), with an 8-week growth cycle. Both GSP0.1 and GSP0.3 showed significantly higher growth performance (final body weight, FBW; weight gain rate, WGR; specific growth rate, SGR) than the NC group, but significantly lower growth performance than the PC group ( P <0.05). However, it was found that there was no significant difference in the body composition of the whole shrimp between the experimental groups. Compared to the PC group, the GSP0.3 group exhibited significantly elevated levels of antioxidant enzymes, total antioxidant capacities (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) ( P <0.05). Additionally, significant differences were observed between the PC and GSP0.3 groups regarding the expression levels of sod , cat , and gsh-px (P<0.05). And there was a better morphological organization of shrimp hepatopancreas in the GSP0.3 group than in all other groups. In comparison with the PC group, there was no significant difference in shrimp survival rates after ammonia nitrogen stress with ginseng saponins added ( P >0.05). Whereas, in terms of the relative expression levels of the corresponding genes, in shrimp of the GSP0.3 group, the relative expression of antioxidant-related genes sod , cat , and gsh-px were significantly higher than that of the PC group ( P <0.05). Caspase3 and p53 , along with bcl-2 and bax , were found to be significantly more expressed in shrimp of the GSP0.3 group than in all other groups ( P <0.05). These findings imply that in addition to improving growth performance, adding ginseng saponins at a concentration of 11% fishmeal could improve the antioxidant capacity of L. vannamei as well as its resistance to stress. Therefore, ginseng saponins can be utilized as a functional additive to increase L. vannamei growth performance, enhance antioxidant capacity, and reduce stress in low-fishmeal diets, 0.3% of ginseng saponins is optimal.

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

The winners of Rising Stars in Plant Sciences 2024 - Rong Chen; Xiaolei Liu; Xiaofeng Cui (Molecular Plant, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Nitrogen removal performance and mechanism in constructed wetlands under saline conditions: Role of Canna indica inoculated with Piriformospora indica - Naxin Cui; Min Cai; Xu Zhang; Rong Zeng; Li Zhou; Guifa Chen; Guoyan Zou (Bioresource Technology, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Mechanism of tartaric acid promoting CuO/H2O2 Fenton-like degradation of sarafloxacin - Bin Ou; Hongwei Rong; Baihui Cui; Jie Zhang; Dabin Guo (Journal of Environmental Chemical Engineering, 2024)

Synthesis and evaluation of a novel cross-linked biochar/ferric chloride hybrid material for integrated coagulation and adsorption of turbidity and humic acid from synthetic wastewater: Implications for sludge valorisation - Pamphile Ndagijimana; Hongwei Rong; Luchun Duan; Shitian Li; François Nkinahamira; Jean Claude Hakizimana; Akash Kumar; Moses Akintayo Aborisade; Pancras Ndokoye; Baihui Cui; Dabin Guo; Ravi Naidu (Environmental Research, 2024)

Removal of the organophosphorus scale inhibitor potassium hexamethylenediamine tetramethylphosphonate (HDTMPA·K6) from industrial wastewater using UV oxidation, flocculation, and the Fenton reaction - LiChao Zhang; Yawen Luo; Wensu Gao; Guiqiao Wang; Jinzhi Cui; Yaxin Lu; Xing Rong; Zhongfa Cheng; Canzhu Gao (Journal of Water Process Engineering, 2024)

Assessing bioenergy prospects of algal biomass and yard waste using an integrated hydrothermal carbonization and pyrolysis (HTC–PY): A detailed emission–to–ash characterization via diverse hyphenated analytical techniques and modelling strategies - Akash Kumar; Imtiaz Ali Jamro; Hongwei Rong; Lata Kumari; Azhar Ali Laghari; Baihui Cui; Moses Akintayo Aborisade; Belay Tafa Oba; François Nkinahamira; Pamphile Ndagijimana; Shahdev Sajnani; Waheed Ali Bhagat; et al. (Chemical Engineering Journal, 2024)

Investigation of the Inhibitory Effects of Illicium verum Essential Oil Nanoemulsion on Fusarium proliferatum via Combined Transcriptomics and Metabolomics Analysis - Cui-Qiong Ling; Hong-Xin Liao; Jin-Rui Wen; Hong-Yan Nie; Li-Yan Zhang; Fu-Rong Xu; Yong-Xian Cheng; Xian Dong (Current Microbiology, 2024)

Seasonality and potential generation mechanisms of submesoscale processes in the northern Bay of Bengal - Yifei Zhou; Wei Duan; Haijin Cao; Guidi Zhou; Rong Cui; Xuhua Cheng (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Chemical methods to remove microplastics from wastewater: A review - Baihui Cui; Hongwei Rong; Tingting Tian; Dabin Guo; Luchun Duan; François Nkinahamira; Pamphile Ndagijimana; Wangwang Yan; Ravi Naidu (Environmental Research, 2024)

An injectable antibacterial hydrogel with bacterial-targeting properties for subcutaneous suppuration treatment - Yongchang Tian; Rong Zhang; Jiaming Cui; Yaowei Zhu; Minghui Sun; Ian W. Hamley; Chunsheng Xiao; Li Chen (Chemical Engineering Journal, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Synthesis, antifungal activity, 3D-QSAR, and molecular docking study of novel anethole-derived hydroxamate compounds - Yucheng Cui; Rong Li; Wengui Duan; Bo Cen; Guishan Lin; Kaiyue Wu (Phytochemistry Letters, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Effect of topographic slope on the interaction between debris flows and riparian forests - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Dong-ri Song; Wan-yu Zhao; Ke Jin (Landslides, 2024)

Conductive nanofiltration membranes via in situ PEDOT-polymerization for electro-assisted membrane fouling mitigation - Tian-Zhi Jia; Ru Feng; Chun Cui; Qian Chen; Levente Cseri; Rong-Fei Zhou; Gyorgy Szekely; Xue-Li Cao; Shi-Peng Sun (Water Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Rapid colorimetric and fluorescence identification of Pinelliae Rhizoma and adulterate Rhizoma Typhonii Flagelliformis using direct-LAMP assay - Huilin Li; Jiaqi Cui; Hongling Chen; Hongying Li; Yuchen Xie; Wenjun Song; Rong Chen (Food Chemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Antiferromagnetic imaging via ptychographic phase retrieval - Jizhe Cui; Haozhi Sha; Wenfeng Yang; Rong Yu (Science Bulletin, 2024)

Modulating conjugated microporous polymers via cyclization as a remarkable photo-enhanced uranium recovery platform - Xiu Wang; Wei Xu; Wei-Rong Cui (Journal of Hazardous Materials, 2024)

Molecular dynamics simulation and experimental analysis of nucleation and growth mechanism of mixed inorganic salts in supercritical water - Siqi Rong; Ruoyu Wang; Anlan Xie; Zhiyong Peng; Peng Cao; Mingyi Zhang; Jinhua Cui; Yunan Chen; Liejin Guo (Chemical Engineering Journal, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Lipid characteristics of lung tissue in silicosis rat model were studied based on lipid metabolomics - Hailan He; Rong Qi; Jie Cui; Mingming Liu; Bo Guan; Yufan Zhou; Yingshu Zhang; Xiaohui Hao; Hongli Wang; Heliang Liu (Toxicology Letters, 2024)

Ecosystem health evaluation of urban rivers based on multitrophic aquatic organisms - Zhen Cui; Wenting Fan; Cheng Chen; Kangle Mo; Qiuwen Chen; Qiang Zhang; Rong He (Journal of Environmental Management, 2024)

Transpiration-mimicking wood-based microfluidic aluminum-air batteries: Green power sources for miniaturized applications - Wei Wang; Liu-Liu Shen; Peiran Wu; Hui Yu; Jiansong Wang; Yipu Xu; Xiangzun Dong; Xuanxuan Cui; Gui-Rong Zhang; Donghai Mei (Chemical Engineering Journal, 2024)

Large-scale synthesis of SiOC composites for stable Li-ion battery anode and dendrite-free Li metal deposition - Shangze Fan; Jiangjiang Zhang; Shiqiang Cui; Lanli Chen; Xuemin Chen; Jinsheng Rong; Wenxin Wang; Yaran Liu; Jing-Tai Zhao (Chemical Engineering Journal, 2024)

Pedotransfer functions for predicting bulk density of coastal soils in East China - Guanghui ZHENG; Caixia JIAO; Xianli XIE; Xuefeng CUI; Gang SHANG; Chengyi ZHAO; Rong ZENG (Pedosphere, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Fracture and porosity evolution of coal under uniaxial compression: An in-situ X-ray tomography study - Yanbin Yu; Zhaoxu Qiu; Weimin Cheng; Qi Yang; Wenting Cui; Kang Rong; Yunfei Li (Geomechanics for Energy and the Environment, 2023)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Research progress of main synthetic catalysts used in biomass pyrolysis - Hongwei Rong; Penghong He; Yuxin Luo; Haizhen Cai; Mahmood Laghari; Dabin Guo; Yan Ren; Baihui Cui (Process Safety and Environmental Protection, 2023)

Heating performance, exergy, and economic analysis of a heat pump drying system with an independent operating ability for drying shiitake mushrooms - Taiyang Xiao; Rong Feng; Xingchen Zhao; Yang Han; Machao Guo; Jiahui Wu; Hong Cui (Journal of Cleaner Production, 2023)

Metabonomics analysis of microalga Scenedesmus obliquus under ciprofloxacin stress - Yue Wang; Weihao Ning; Shengnan Li; Changfei Gao; Rong Cui; Wanqian Guo; Jo-Shu Chang; Shih-Hsin Ho (Environmental Research, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Quantification of multiple environmental controls on lipid biomarkers in common marine diatoms and dinoflagellates - Zhong Cao; Rong Bi; Chuanli Zhang; Jiaxuan Cui; Li Li; Yang Ding; Meixun Zhao (Marine Biology, 2023)

Prostate Cancer, Oxidative Stress, and Antioxidant Phytochemicals: A Brief Review - Shanyi Li; Tong Cai; Shichen Cui; Fangmin Liu; Rong Hu; Wenji Li (Current Pharmacology Reports, 2023)

Metal-organic framework composite Mn/Fe-MOF@Pd with peroxidase-like activities for sensitive colorimetric detection of hydroquinone - Die Deng; Ya Wang; Shaohua Wen; Yujie Kang; Xiaoyan Cui; Rong Tang; Xiupei Yang (Analytica Chimica Acta, 2023)

Nitrogen and sulfur co-doped carbon quantum dots as “on-off-on” fluorescence probes to detect Hg2+ and MnO4− and improving the photostability of Rhodamine B - Wensu Gao; Shurong Zhang; Guiqiao Wang; Jinzhi Cui; Yaxin Lu; Xing Rong; Yawen Luo; LiChao Zhang; Zhongfa Cheng; Canzhu Gao (Analytica Chimica Acta, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A review on activated carbon/ graphene composite-based materials: Synthesis and applications - Pamphile Ndagijimana; Hongwei Rong; Pancras Ndokoye; Jean Pierre Mwizerwa; François Nkinahamira; Shiyi Luo; Dabin Guo; Baihui Cui (Journal of Cleaner Production, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Simultaneous removal of sulfamethoxazole during fermentative production of short-chain fatty acids - Yue Wang; Rongrong Lin; Yushuang Cao; Shuangfei Li; Rong Cui; Wanqian Guo; Shih-Hsin Ho; Yoong Kit Leong; Duu-Jong Lee; Jo-Shu Chang (Bioresource Technology, 2023)

Influence of GI configurations and wall thermal effects on flow structure and pollutant dispersion within urban street canyons - Peng-Yi Cui; Rong Ji; Lai He; Zhen Zhang; Yang Luo; Yong Yang; Yuan-Dong Huang (Building and Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Ultra-stable 3D pyridinium salt-based polymeric network nanotrap for selective 99TcO4-/ReO4- capture via hydrophobic and steric engineering - Wei Xu; Xiu Wang; Yibao Li; Wei-Rong Cui (Journal of Hazardous Materials, 2023)

Faba bean above-ground biomass and bean yield estimation based on consumer-grade unmanned aerial vehicle RGB images and ensemble learning - Yishan Ji; Rong Liu; Yonggui Xiao; Yuxing Cui; Zhen Chen; Xuxiao Zong; Tao Yang (Precision Agriculture, 2023)

Towards advanced mariculture wastewater treatment by bacterial-algal symbiosis system with different bacteria and algae inoculation ratios - Hongwei Rong; Yingying Li; Jingyin Wang; Qi Zhang; Baihui Cui; Dabin Guo (Journal of Water Process Engineering, 2023)

PSMD4 drives progression of hepatocellular carcinoma via Akt/COX2 pathway and p53 inhibition - Jiamin Zhang; Shu Fang; Fanghao Rong; Miaomiao Jia; Yunpeng Wang; Huixian Cui; Peipei Hao (Human Cell, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Effects of Inclination Angles on the Hydrodynamics of Knotless Net Panels in Currents - Gang Wang; Yong Cui; Changtao Guan; Pihai Gong; Rong Wan (Journal of Marine Science and Engineering, 2023)
Knotless nets have been extensively used in sea cages and offshore fish farms; the explicit illustrations of local flow patterns and subjected hydrodynamic loads have practical implications for the safe operations of aquaculture pens in open oceans. However, the effects of inclination angles of knotless nets on local flow patterns have not yet been fully discussed. In this paper, the effects of inclination angles on local time-averaged and instantaneous flow fields, velocity reductions and force coefficients are investigated using a k-ω shear stress transport-improved delayed detached eddy simulation (SST-IDDES) high-fidelity turbulence model. It is demonstrated that the inclination angles have dominant effects on the time-averaged velocity magnitudes around the net meshes. Secondly, the considerable flow interactions amongst the transverse and longitudinal net meshes, as well as cross-flow effects, are observed but weakened with the inclination angles. Thirdly, the profiles of velocity decelerations behind the net panels for 0∘–45∘ are not as trivial as those for 45∘–90∘. The associations between the embedded mechanism of subjected loads and pressure fields are established to analyse the current loads on nets in small inclination angles. The inclination angles are finally elaborated into the area-averaged velocity reduction and screen force models, then the improved characteristics are validated against the experimental data.

OsCIP1, a secreted protein, binds to and stabilizes OsCR4 to promote aleurone layer development, seed germination and early seedling growth in rice - Lin-Lin Yan; Jing Mi; Can-Can Shen; Rong Qian; Jiao Wang; Cui-Xia Pu; Ying Sun (Plant Science, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Debris flow characteristics of the compound channels with vegetated floodplains - Wen-rong Cui; Jian-gang Chen; Xiao-qing Chen; Jin-bo Tang; Ke Jin (Science of The Total Environment, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Diagnosis of atmospheric circulation shifts in the central Tibetan Plateau: Evidence from stable isotopes - Yao Li; Wusheng Yu; Lide Tian; Stephen Lewis; Kei Yoshimura; Cheng Wang; Jiangpeng Cui; Yaoming Ma; Rong Guo; Jingyi Zhang; Zhaowei Jing; Lili Shao; et al. (Atmospheric Research, 2023)

Targeted isolation of antitubercular cycloheptapeptides and an unusual pyrroloindoline-containing new analog, asperpyrroindotide A, using LC–MS/MS-based molecular networking - Yi-Qian Han; Qun Zhang; Wei-Feng Xu; Yang Hai; Rong Chao; Cui-Fang Wang; Xue-Mei Hou; Mei-Yan Wei; Yu-Cheng Gu; Chang-Yun Wang; Chang-Lun Shao (Marine Life Science & Technology, 2023)
Further insights on the secondary metabolites of a soft coral-derived fungus Aspergillus versicolor under the guidance of MS/MS-based molecular networking led to the isolation of seven known cycloheptapeptides, namely, asperversiamides A–C ( 1 – 3 ) and asperheptatides A–D ( 4 – 7 ) and an unusual pyrroloindoline-containing new cycloheptapeptide, asperpyrroindotide A ( 8 ). The structure of 8 was elucidated by comprehensive spectroscopic data analysis, and its absolute configuration was determined by advanced Marfey’s method. The semisynthetic transformation of 1 into 8 was successfully achieved and the reaction conditions were optimized. Additionally, a series of new derivatives ( 10 − 19 ) of asperversiamide A ( 1 ) was semi-synthesized and their anti-tubercular activities were evaluated against Mycobacterium tuberculosis H37Ra. The preliminary structure−activity relationships revealed that the serine hydroxy groups and the tryptophan residue are important to the activity.

Occurrence, distribution, and driving factors of current-use pesticides in commonly cultivated crops and their potential risks to non-target organisms: A case study in Hainan, China - Huadong Tan; Qiumin Wu; Rong Hao; Chuanmi Wang; Jinlin Zhai; Qinfen Li; Yanmei Cui; Chunyuan Wu (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Silencing circ_0074371 inhibits the progression of sepsis-induced acute kidney injury by regulating miR-330-5p/ELK1 axis - Qiu-yuan Wang; Rong-rong Zhang; Long Cui; Ya-ping Sun (Mammalian Genome, 2022)

NGF/TrkA promotes the vitality, migration and adhesion of bone marrow stromal cells in hypoxia by regulating the Nrf2 pathway - Cui-Ni Fang; Hai-Qun Tan; Ao-Bo Song; Ni Jiang; Qian-Rong Liu; Tao Song (Metabolic Brain Disease, 2022)

Clinical evidence of dietary supplementation with sesame on cardiovascular risk factors: An updated meta-analysis of randomized controlled trials - Haohai Huang; Guanghui Zhou; Rong Pu; Yejia Cui; Dan Liao (Critical Reviews in Food Science and Nutrition, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Comment on “Relationship of Circulating Copper Level with Gestational Diabetes Mellitus: a Meta-analysis and Systemic Review” - Shu-ping Li; Xiao-ping Zhang; Xin-hong Cui; Li-juan Zhao; Yan-jun Rong (Biological Trace Element Research, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Neiella holothuriorum sp. nov., isolated from the gut of a sea cucumber Apostichopus japonicus - Xin-Feng Bai; Xue-Lian Lv; Xue Liu; Ting-Ting Cui; Mian-Song Zhang; Ning Ding; Chang-Heng Liu; Ai-Rong Jia (Antonie van Leeuwenhoek, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Clinical characteristics of 967 children with pertussis: a single-center analysis over an 8-year period in Beijing, China - Limin Kang; Xiaodai Cui; Jin Fu; Wenpeng Wang; Li Li; Tiegeng Li; Xiaoying Wang; Fei Xiao; Huixue Jia; Rong Mi; Xinlin Hou (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Phenolic glycosides and flavonoids with antioxidant and anticancer activities from Desmodium caudatum - Qian-Nan Xu; Dan Zhu; Guang-Hui Wang; Ting Lin; Cui-Ling Sun; Rong Ding; Wen-Jing Tian; Hai-Feng Chen (Natural Product Research, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Function identification of miR394 in tomato resistance to Phytophthora infestans - Yuan-Yuan Zhang; Yu-Hui Hong; Ya-Rong Liu; Jun Cui; Yu-Shi Luan (Plant Cell Reports, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Biocontrol mechanism of Myxococcus fulvus B25-I-3 against Phytophthora infestans and its control efficiency on potato late blight - Zhi Hua Wu; Qiang Ma; Zhi Ning Sun; Hai Chen Cui; Hui Rong Liu (Folia Microbiologica, 2021)

Mesoscale wind stress-SST coupling induced feedback to the ocean in the western coast of South America - Chaoran Cui; Rong-Hua Zhang; Yanzhou Wei; Hongna Wang (Journal of Oceanology and Limnology, 2021)

Regenerable, anti-biofouling covalent organic frameworks for monitoring and extraction of uranium from seawater - Yi-Di Wu; Wei-Rong Cui; Cheng-Rong Zhang; Ru-Ping Liang; Jian-Ding Qiu (Environmental Chemistry Letters, 2021)

Nanomaterials for Airborne Virus Inactivation: A Short Review - Rong Li; Long Cui; Meijuan Chen; Yu Huang (Aerosol Science and Engineering, 2021)

Overexpression of thioredoxin reductase 1 can reduce DNA damage, mitochondrial autophagy and endoplasmic reticulum stress in Parkinson's disease - Zihua Liu; Qiang Ye; Fang Wang; Yanan Guo; Rong Cui; Jianlin Wang; Degui Wang (Experimental Brain Research, 2021)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Soil bio-cementation using an improved 2-step injection method - Ming-Juan Cui; Jun-Jie Zheng; Rong-Jun Zhang; Han-Jiang Lai (Arabian Journal of Geosciences, 2020)

Correction of seismic attribute-based small-structure prediction errors using GPR data—A case study of the Shuguang Coal Mine, Shanxi - Cui Fan; Zhao Zhi-Rong; Du Yun-Fei; Bai Yu; Xu Chang-Qing; Jia Xiao-Feng (Applied Geophysics, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Heat-air-moisture coupled model for radon migration in a porous media - Yu Cui; Shengyang Feng; Puxin Chen; Yongjun Ye; Yurong Wu; Ce Li; Rong Yang; Hong Wang (Environmental Science and Pollution Research, 2020)

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

GDP: an open-source GNSS data preprocessing toolkit - Zhengsheng Chen; Yang Cui; Linyang Li; Qinghua Zhang; Zhiping Lu; Xuerui Li; Yingcai Kuang; Kaichun Yang; Fengjuan Rong (GPS Solutions, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

Representing surface wind stress response to mesoscale SST perturbations in western coast of South America using Tikhonov regularization method - Chaoran Cui; Rong-Hua Zhang; Hongna Wang; Yanzhou Wei (Journal of Oceanology and Limnology, 2020)

Simulating Spatial Variation of Soil Carbon Content in the Yellow River Delta: Comparative Analysis of Two Artificial Neural Network Models - Chen Wang; Yuan Cui; Ziwen Ma; Yutong Guo; Qian Wang; Yujiao Xiu; Rong Xiao; Mingxiang Zhang (Wetlands, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Effects of shallow groundwater table fluctuations on nitrogen in the groundwater and soil profile in the nearshore vegetable fields of Erhai Lake, southwest China - Dan Zhang; Maopan Fan; Hongbin Liu; Rong Wang; Jixia Zhao; Yanxian Yang; Rongyang Cui; Anqiang Chen (Journal of Soils and Sediments, 2020)

Cell bioreactor culture of Orostachys cartilaginous A. Bor. and involvement of nitric oxide in methyl jasmonate-induced flavonoid synthesis - Yue-Jun Hao; Xi-Hua Cui; Jin-Rong Li; Xiao-Li An; Hao-Ding Sun; Xuan-Chun Piao; Mei-Lan Lian (Acta Physiologiae Plantarum, 2020)

Engagement of MicroRNA-155 in Exaggerated Oxidative Stress Signal and TRPA1 in the Dorsal Horn of the Spinal Cord and Neuropathic Pain During Chemotherapeutic Oxaliplatin - Fenghua Miao; Rong Wang; Guozhen Cui; Xiaoguang Li; Ting Wang; Xue Li (Neurotoxicity Research, 2019)

Protective approaches and mechanisms of microencapsulation to the survival of probiotic bacteria during processing, storage and gastrointestinal digestion: A review - Huan Liu; Steve W. Cui; Maoshen Chen; Yue li; Rong Liang; Feifei Xu; Fang Zhong (Critical Reviews in Food Science and Nutrition, 2019)

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Genetic diversity of 324 cultivated tomato germplasm resources using agronomic traits and InDel markers - Lan Jin; Liping Zhao; Yinlei Wang; Rong Zhou; Liuxia Song; Liping Xu; Xia Cui; Ren Li; Wengui Yu; Tongmin Zhao (Euphytica, 2019)

Levels of phthalate acid esters and sex hormones and their possible sources in traffic-patrol policemen in Chongqing - Lu Lu; Honghui Rong; Chong Wu; Bo Cui; Yujing Huang; Yao Tan; Ling Zhang; Yi Peng; Jose M. Garcia; Ji-an Chen (Environmental Science and Pollution Research, 2019)

Study on nitrogen removal from rice paddy field drainage by interaction of plant species and hydraulic conditions in eco-ditches - Huanhao Han; Yuanlai Cui; Rong Gao; Ying Huang; Yufeng Luo; Shizhou Shen (Environmental Science and Pollution Research, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Benzene metabolite 1,2,4-benzenetriol changes DNA methylation and histone acetylation of erythroid-specific genes in K562 cells - Chun-Hong Yu; Yang Li; Xiao Zhao; Shui-Qing Yang; Lei Li; Ning-Xuan Cui; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

The complete mitochondrial genome of an endangered reef gastropods Trochus pyramis - Zhi-ying Zhao; Zhi-gang Tu; Jing Cui; Li-rong Bai (Conservation Genetics Resources, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Fermentation Kinetics of Enzymatic Hydrolysis Bagasse Solutions for Producing l-Lactic Acid - Yuanyuan Cui; Rong Liu; Linlin Xu; Wenjing Zheng; Weidong Sun (Sugar Tech, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Functional Investigation of a GRIN2A Variant Associated with Rolandic Epilepsy - Xing-Xing Xu; Xiao-Rong Liu; Cui-Ying Fan; Jin-Xing Lai; Yi-Wu Shi; Wei Yang; Tao Su; Jun-Yu Xu; Jian-Hong Luo; Wei-Ping Liao (Neuroscience Bulletin, 2018)

Anomalous gray matter structural networks in recent onset post-traumatic stress disorder - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Jian Zhang; Fan Guo; Qing-Rong Tan; Mei Shi; Kang Liu; Yi-Bin Xi; Nan-Yin Zhang; Xiao-Liang Zhang; Yong He; et al. (Brain Imaging and Behavior, 2018)

Characterization of an endangered marine strombid gastropod Strombus luhuanus complete mitochondrial genome - Zhi-ying Zhao; Zhi-gang Tu; Li-rong Bai; Jing Cui (Conservation Genetics Resources, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

An efficient method for developing polymorphic microsatellite markers from high-throughput transcriptome sequencing: a case study of hexaploid oil-tea camellia (Camellia oleifera) - Xiangyan Cui; Xiaomao Huang; Jiaming Chen; Xiaoqiang Yang; Jun Rong (Euphytica, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Salidroside Ameliorates Diabetic Neuropathic Pain in Rats by Inhibiting Neuroinflammation - Gui-Lian Ni; Rong Cui; Ai-Min Shao; Zhong-Min Wu (Journal of Molecular Neuroscience, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Phosphorylation of histone H3 on Ser-10 by Aurora B is essential for chromosome condensation in porcine embryos during the first mitotic division - Changchao Chen; Zixiao Zhang; Panpan Cui; Yaya Liao; Yue Zhang; Lingyun Yao; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2017)

Abnormal Effective Connectivity in the Brain is Involved in Auditory Verbal Hallucinations in Schizophrenia - Baojuan Li; Long-Biao Cui; Yi-Bin Xi; Karl J. Friston; Fan Guo; Hua-Ning Wang; Lin-Chuan Zhang; Yuan-Han Bai; Qing-Rong Tan; Hong Yin; Hongbing Lu (Neuroscience Bulletin, 2017)

Involvement of the miR-462/731 cluster in hypoxia response in Megalobrama amblycephala - Cui-Hong Huang; Nan Chen; Chun-Xiao Huang; Bao Zhang; Meng Wu; Lei He; Hong Liu; Rong Tang; Wei-Min Wang; Huan-Ling Wang (Fish Physiology and Biochemistry, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

Sleep and Cognitive Abnormalities in Acute Minor Thalamic Infarction - Wei Wu; Linyang Cui; Ying Fu; Qianqian Tian; Lei Liu; Xuan Zhang; Ning Du; Ying Chen; Zhijun Qiu; Yijun Song; Fu-Dong Shi; Rong Xue (Neuroscience Bulletin, 2016)

Toxicity of combined chromium(VI) and phenanthrene pollution on the seed germination, stem lengths, and fresh weights of higher plants - Shuangqing Hu; Hairong Gu; Chunyan Cui; Rong Ji (Environmental Science and Pollution Research, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Effects of silica exposure on the cardiac and renal inflammatory and fibrotic response and the antagonistic role of interleukin-1 beta in C57BL/6 mice - Jiali Guo; Tingming Shi; Xiuqing Cui; Yi Rong; Ting Zhou; Zhihong Zhang; Yuewei Liu; Yan Shen; Weihong Chen (Archives of Toxicology, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

The involvement of c-Myc in the DNA double-strand break repair via regulating radiation-induced phosphorylation of ATM and DNA-PKcs activity - Fengmei Cui; Rong Fan; Qiu Chen; Yongming He; Man Song; Zengfu Shang; Shimeng Zhang; Wei Zhu; Jianping Cao; Hua Guan; Ping-Kun Zhou (Molecular and Cellular Biochemistry, 2015)

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .

Failure modes of reinforced concrete columns of buildings under debris flow impact - Chao Zeng; Peng Cui; Zhiman Su; Yu Lei; Rong Chen (Landslides, 2015)

Multilocus sequence typing analysis of Cronobacter spp. isolated from China - Jing-Hua Cui; Xiao-Li Du; Rong-Jie Wei; Hai-Jian Zhou; Wei Li; Stephen Forsythe; Zhi-Gang Cui (Archives of Microbiology, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Application of molecularly imprinted polymers in wastewater treatment: a review - Dan-Lian Huang; Rong-Zhong Wang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Piao Xu; Bing-An Lu; Juan-Juan Xu; Cong Wang; Chao Huang (Environmental Science and Pollution Research, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Halopenitus salinus sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

The checkpoint 1 kinase inhibitor LY2603618 induces cell cycle arrest, DNA damage response and autophagy in cancer cells - Feng-Ze Wang; Hong-rong Fei; Ying-Jie Cui; Ying-Kun Sun; Zhao-Mei Li; Xue-Ying Wang; Xiao-Yi Yang; Ji-Guo Zhang; Bao-Liang Sun (Apoptosis, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

MiR-335, an Adipogenesis-Related MicroRNA, is Involved in Adipose Tissue Inflammation - Lu Zhu; Ling Chen; Chun-Mei Shi; Guang-Feng Xu; Lu-Lian Xu; Ling-Ling Zhu; Xi-Rong Guo; Yuhui Ni; Yan Cui; Chenbo Ji (Cell Biochemistry and Biophysics, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Distribution and pollution, toxicity and risk assessment of heavy metals in sediments from urban and rural rivers of the Pearl River delta in southern China - Rong Xiao; Junhong Bai; Laibin Huang; Honggang Zhang; Baoshan Cui; Xinhui Liu (Ecotoxicology, 2013)

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

Neutralization of interleukin-1 beta attenuates silica-induced lung inflammation and fibrosis in C57BL/6 mice - Jiali Guo; Nali Gu; Jie Chen; Tingming Shi; Yun Zhou; Yi Rong; Ting Zhou; Wenxiang Yang; Xiuqing Cui; Weihong Chen (Archives of Toxicology, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

A chloroplast membrane protein LTO1/AtVKOR involving in redox regulation and ROS homeostasis - Ying Lu; Hua-Rong Wang; Han Li; Hao-Ran Cui; Yue-Guang Feng; Xiao-Yun Wang (Plant Cell Reports, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Nonstructural protein-1 of respiratory syncytial virus regulates HOX gene expression through interacting with histone - Yu-rong Tan; Dan Peng; Cui-mei Chen; Xiao-qun Qin (Molecular Biology Reports, 2013)

The binding characteristics of the interaction between 3-(2-cyanoethyl) cytosine and human serum albumin - Feng-Ling Cui; Guang-Quan Hui; Rui-Na Huo; Gui-Rong Qu (Molecular Biology Reports, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Effects of Atorvastatin on Pathological Changes in Brain Tissue and Plasma MMP-9 in Rats with Intracerebral Hemorrhage - Jing-Jing Cui; Dong Wang; Fei Gao; Yue-Rong Li (Cell Biochemistry and Biophysics, 2012)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Highly efficient and catalyst-free synthesis of substituted thioureas in water - Shi-Feng Gan; Jie-Ping Wan; Yuan-Jiang Pan; Cui-Rong Sun (Molecular Diversity, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Trace element contaminations of roadside soils from two cultivated wetlands after abandonment in a typical plateau lakeshore, China - Junhong Bai; Qinggai Wang; Kejiang Zhang; Baoshan Cui; Xinhui Liu; Laibin Huang; Rong Xiao; Haifeng Gao (Stochastic Environmental Research and Risk Assessment, 2011)

Nitrification potential of marsh soils from two natural saline–alkaline wetlands - Junhong Bai; Haifeng Gao; Wei Deng; Zhifeng Yang; Baoshan Cui; Rong Xiao (Biology and Fertility of Soils, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

Preliminary studies on the chemical characterization and antioxidant properties of acidic polysaccharides from Sargassum fusiforme - Jing Zhou; Nan Hu; Ya-lin Wu; Yuan-jiang Pan; Cui-rong Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Characterization of impurities in the bulk drug lisinopril by liquid chromatography/ion trap spectrometry - Pei-xi Zhu; Dan-hua Wang; Cui-rong Sun; Zhi-quan Shen (Journal of Zhejiang University-SCIENCE B, 2008)

Akt/PKB interacts with the histone H3 methyltransferase SETDB1 and coordinates to silence gene expression - Haidong Gao; Zhigang Yu; Dongsong Bi; Liyu Jiang; Yazhou Cui; Jingzhong Sun; Rong Ma (Molecular and Cellular Biochemistry, 2007)

Apelin suppresses apoptosis of human osteoblasts - Hui Xie; Ling-Qing Yuan; Xiang-Hang Luo; Jiao Huang; Rong-Rong Cui; Li-Juan Guo; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (Apoptosis, 2007)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)

Enhanced Methane Production from Anaerobic Digestion of Disintegrated and Deproteinized Excess Sludge - Rong Cui; Deokjin Jahng (Biotechnology Letters, 2006)

Genetic diversity of alligator weed in China by RAPD analysis - Cheng-Yuan Xu; Wen-Ju Zhang; Cui-Zhang Fu; Bao-Rong Lu (Biodiversity and Conservation, 2003)

ANALYSIS OF THREE MARINE FISH CELL LINES BY RAPD ASSAY - HUA-RONG GUO; SHI-CUI ZHANG; SHANG-LIANG TONG; JIAN-HAI XIANG (In Vitro Cellular & Developmental Biology - Animal, 2001)

High Resolution DC EEG of the Bereitschaftspotential Preceding Anatomically Congruent Versus Spatially Congruent Bimanual Finger Movements - Rong-Qing Cui; Lüder Deecke (Brain Topography, 1999)

Solvent assistance in regiospecific disulfide formation in dimethylsulfoxide - James P. Tam; Xiang Chao Dong; Cui Rong Wu (International Journal of Peptide Research and Therapeutics, 1999)

High Resolution DC-EEG Analysis of the Bereitschaftspotential and Post Movement Onset Potentials Accompanying Uni- or Bilateral Voluntary Finger Movements - Rong Qing Cui; Lüder Deecke (Brain Topography, 1999)